Potentialités de l’écotourisme et géotourisme aux provinces de Tantan, Tarfaya et Layoune (Sahara Atlantique marocain) - Amimi, Taha; Ouhnine, Radouane; Chao, Jamal; Elbelrhiti, Hicham; Koffi, Avy Stéphane (European Scientific Journal, ESJ, 2017)
Tantan, Tarfaya and Laayoune provinces, which belong to the Moroccan Atlantic Sahara, are characterized by exceptional geo and ecotourism potentials. In this context, singing dunes, sand rivers and the presence of several wadis mouth’s in such desert environment could constitute a locomotive for the development of green and geological tourism. Indeed, the studied region presents Eco and Geo-tourism potentials, combining ecological sites classified by the RAMSAR convention as the Khnifis lagoon, the wadis mouth’s including the longest river in Morocco (Oued Draa) with its new national park. Rivers of sand with multitudes sand colours, singing dunes, virgin beaches and sebkhas with the lowest point in Morocco, the sebkha of Tah with an altitude of -55 m adsl.